Enhancing energy security in Malayia: The challenges towards sustainable environment - Sahid E.J.M.; Siang C.C.; Peng L.Y. (Institute of Physics Publishing, 2023)
Energy is known as one of the essential ingredients for economic development and security of energy supply is crucial in ensuring continuous economic development of a country. Malaysia's proven domestic oil reserves are estimated to last for another 25 years, while that of gas for another 39 years as of 2011. Despite the depleting indigenous energy resources, the primary energy demand has continued to grow robustly, at an annual rate of 6.3 percent per year from 1990 to 2010, while the primary energy import has grown 7.2% per year and the primary energy export has grown at a slower rate of 1.9% per year. This worrying trend is further compounded by the faster rate of primary oil import averaging 10.5% per year while the primary energy export has shrink at a rate of 1.4% per year. This paper has identified two main concerns namely overdependence on fossil fuel and increasing energy import dependency in creating a precarious position towards energy self-sufficiency. The study will analyse the energy security of the country and explore possible options and challenges in enhancing the energy supply security toward sustainable environment. Published under licence by IOP Publishing Ltd.